Citra Merek, Gaya Hidup, dan Servicescape terhadap Keputusan Pembelian - Suraj Suraj; Dharma Winata Kristanto; Rico Prestasi (Journal of Management and Bussines (JOMB), 2022)
The purpose of the study was to examine and analyze the influence of brand image, lifestyle, and servicescape on purchasing decisions of All Day Bread consumers in Medan City. This research method is descriptive quantitative. The population in this study were customers who made purchases at the All Day Bread Medan Bakery, totaling 1924 customers. Sampling using the Slovin formula, totaling 96 people. Data analysis used the classical assumption test, and the hypothesis test was multiple linear regression analysis. The results showed, a) brand image has a significant value (0.004) smaller than 0.1 and t-count (2.975) is greater than t-table (1.661); b) lifestyle has a significant value (0.005) smaller than 0.1 and t-count (2.891) is greater than t-table (1.661); c) servicescape has a significant value (0.027) smaller than 0.1 and t-count (2.240) is greater than t-table (1.661); d) brand image, lifestyle, and servicesscpae have Fcount value (37.941) greater than Ftable (2.14), and sig (0.000) less than alpha 10 percent (0.1). Conclusions, a) brand image has a positive and significant effect on purchasing decisions on All Day Bread consumers in the city of Medan; b) lifestyle has a positive and significant effect on purchasing decisions on All Day Bread consumers in Medan; c) servicescape has an effect on purchasing decisions for All Day Bread consumers in the city of Medan. Keywords: Brand Image, Lifestyle, Purchase Decision, Servicescape